Development of Arabic language learning curriculum during the COVID-19 pandemic - Ayu Desrani; Zainul Arifin; Suci Ramadhanti Febriani; Bedra Guettaoi (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2022)
The purpose of this study is to find out and analyze the curriculum that is suitable for Arabic language learning during the COVID-19 pandemic.  This research is literature review research because the purpose of this study is to produce a design for the development of an Arabic curriculum during the Covid-19 pandemic based on the results of previous research. The results showed that there are 4 basics in the development of the Arabic language learning curriculum during the pandemic; 1) The compilation of learning objectives must be adapted to the circumstances of the learners and socialized to parents to work together to achieve these goals, 2) The content or content of the material is designed in such a way as to reach the students direct to higher level thinking skills, 3) During the learning process the teacher is required to be as creative as possible to guide the learning of the use of appropriate methods and media is very influential,  4) Evaluation is strongly recommended on a project-based basis to avoid the possibility of students cheating on each other.